2017
DOI: 10.1007/s00127-017-1374-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of DSM-5 posttraumatic stress disorder and its association with suicide attempts: results from the National Epidemiologic Survey on Alcohol and Related Conditions-III

Abstract: The identification of the primary latent trait of PTSD confirms PTSD as an independent psychiatric disorder and helps define PTSD severity in clinical practice and for etiologic research. The accurate specification of PTSD factor structure has implications for treatment efforts and the prevention of suicidal behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
3
7
0
Order By: Relevance
“…Our results align theoretically with recent findings that a general "transdiagnostic" factor as well as several specific factors often underlie psychopathology symptom data (e.g., Chen, Yoon, Harford, & Grant, 2017;Reininghaus et al, 2016;Shevlin, McElroy, Bentall, Reininghaus, & Murphy, 2017). However, traditional confirmatory approaches to bifactor analysis are unlikely to arrive at the complex factor structure uncovered here.…”
Section: A Big-five Personality Factors Data Setsupporting
confidence: 91%
“…Our results align theoretically with recent findings that a general "transdiagnostic" factor as well as several specific factors often underlie psychopathology symptom data (e.g., Chen, Yoon, Harford, & Grant, 2017;Reininghaus et al, 2016;Shevlin, McElroy, Bentall, Reininghaus, & Murphy, 2017). However, traditional confirmatory approaches to bifactor analysis are unlikely to arrive at the complex factor structure uncovered here.…”
Section: A Big-five Personality Factors Data Setsupporting
confidence: 91%
“…Chen and colleagues [38] analyzed the data from 36,309 U.S. adults (≥18 years) from the National Epidemiologic Survey on Alcohol and Related Conditions-III and found that both PTSD and anhedonia were associated with attempting suicide.…”
Section: Resultsmentioning
confidence: 99%
“…PTSD's relationship with suicidal ideation was found to be mediated by the presence of the depressive symptoms it caused; this finding was the strongest support for the use of GST in examining the relationships between PTSD, depression, and suicidality. The results of this study also suggested that one possible cause for the inconsistent significant relationship found between PTSD and suicidality in some studies was this mediating relationship (Chen et al, 2017;Cougle et al, 2009a). As depression is the most common disorder associated with suicide and is commonly found to be comorbid with PTSD and other mental disorders, it is possible that this result indicates that depression is a priming agent for suicidality.…”
Section: Resultssupporting
confidence: 51%
“…Individuals with PTSD are roughly 80% more likely to meet the full criteria for at least one other disorder compared to those without PTSD (APA, 2013). Some of the most common disorders experienced comorbidly with PTSD include depression in general (Cougle et al, 2009a(Cougle et al, , 2009bDorrington et al, 2014;Marshall et al, 2001;Stevens et al,2013) and high-risk samples (Chen, Yoon, Harford, & Grant, 2017;Denhof & Spinaris, 2013Rytwinski, Scur, Feeny, & Youngstrom, 2013;Spinaris et al, 2012); alcohol/substance abuse in both general samples (Neupane, Bramness, & Lien, 2017;Smith et al, 2016) and samples of high-risk populations (Chen et al, 2017;Hellmuth et al, 2012); and Traumatic Brain Injury (especially in military samples) (APA, 2013;Kessler et al, 1995).…”
Section: Ptsd and Comorbiditymentioning
confidence: 99%